Nevirapine mitigates monosodium glutamate induced neurotoxicity and oxidative stress changes in prepubertal mice (Annals of Medical Research, 2021)
None
Keywords: HAART; Monosodium glutamate; Prepubertal; Oxidative stress; Apoptosis.br /